Surveillance of coastal erosion and marine habitat degradation using remote sensing and GIS - Nayak, Ashu; Lalnunthari; Rawat, Atul (International Journal of Aquatic Research and Environmental Studies, 2025)
Accurately identifying coastal regions affected by historical, current, and prospective erosion is essential for effective coastal risk mitigation. In this context, satellite imagery is a significant synoptic and multi-temporal input source. The study employed Geographic Information System (GIS) and satellite imagery tools to map and model coastline change. The long-term patterns of advancement and retreat of the shoreline were assessed using Landsat imagery from the mid-1970s to 2025, followed by predicting and validating a short-term scenario over three years. Two distinct coastal ecosystems, Oceanic and Mediterranean, were examined. Initially, various proxies were examined, facilitating a multi-proxy study. The findings indicated that the approach yielded more precise results in high-energy situations (oceanic) and in areas where the shoreline is not urbanized. The findings underscored the significance of conducting multi-proxy analysis in specific research regions to more accurately delineate shoreline models. Significantly, the studies focused on evaluating uncertainty, essential when research outputs are contemplated for managerial purposes.